A study on the factors influencing cyberbullying behaviors among SNS users - Changbae, Mun; Suaini Sura; Jongchang, Ahn (The Korea Society of Information Technology Services, 2015)
As the explosive growth of SNS users, SNS affects every aspect of our lives. Beyond the individual`s scope there is a powerful influence in society. Now cyber bullying is a big problem of this society. To analyze the relationship between the SNS user features and cyber bullying phenomenon, various SNS user`s personal and social characteristics were set to variables affecting the cyber bullying phenomenon on the SNS. For the research, questionnaire survey was conducted for total 200 subjects among 10~60 age band in each region across the country. We set a research model including the items that are found to be affected in cyber bullying through the prior researches. To analyze interrelation of cyber bullying phenomenon and the general characteristics of SNS users, multiple regression analysis and other analyses were conducted. As a statistical result, we found the correlation among variables and the suggestion points for a SNS platform development direction.